The prevalence of diabetes‐specific emotional distress in people with Type 2 diabetes: a systematic review and meta‐analysis - Perrin, N. E.; Davies, M. J.; Robertson, N.; Snoek, F. J.; Khunti, K. (Diabetic medicine, 2017)
Aims Psychological comorbidity, such as depression and/or diabetes‐specific emotional distress (diabetes distress), is widespread in people with Type 2 diabetes and is associated with poorer treatment outcomes. Although extensive research into the prevalence of depression has been conducted, the same attention has not been given to diabetes distress. The aim of this systematic review was to determine the overall prevalence of diabetes distress in people with Type 2 diabetes. Methods Seven databases were searched to identify potentially relevant studies; eligible studies (adult population aged > 18 years with Type 2 diabetes and an outcome measure of diabetes distress) were selected and appraised independently by two reviewers. Multiple fixed‐ and random‐effects meta‐analyses were performed to synthesize the data; with primary analyses to determine the overall prevalence of diabetes distress in people with Type 2 diabetes, and secondary meta‐analyses and meta‐regression to explore the prevalence across different variables. Results Fifty‐five studies (n = 36 998) were included in the meta‐analysis and demonstrated an overall prevalence of 36% for diabetes distress in people with Type 2 diabetes. Prevalence of diabetes distress was significantly higher in samples with a higher prevalence of comorbid depressive symptoms and a female sample majority. Conclusions Diabetes distress is a prominent issue in people with Type 2 diabetes that is associated with female gender and comorbid depressive symptoms. It is important to consider the relationship between diabetes distress and depression, and the significant overlap between conditions. Further work is needed to explore psychological comorbidity in Type 2 diabetes to better understand how best to identify and appropriately treat individuals.